The relationship between adherence to the Mediterranean diet and abdominal obesity and related metabolic risk: Mediterranean diet and obesity with metabolic disorder - Abu Salma, Baha’a (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction: The Mediterranean diet is rich in bioactive compounds that have protective effects against metabolic disorders, and insulin resistance and reduce weight. Objective: To explore the relationship between adherence to the Mediterranean diet and central obesity as well as related metabolic disorders. Material and Methods: A cross-sectional study was conducted on 480 participants between the ages (18 - 65) years who were diagnosed with metabolic disorders. Data was collected using a structured questionnaire to determine socio-demographic data, anthropometric measurements, and biochemical laboratory results of metabolic parameters. The Mediterranean Diet Adherence Screener was used to measure the adherence of participants to the Mediterranean Diet. Pearson correlation and multiple linear regression were used to measure the strength and magnitude of association between parameters. Results: The results show that higher adherence to Mediterranean Diet has significantly (P< 0.05) and inversely associated with triglyceride, cholesterol, LDL- cholesterol, cholesterol/ HDL ratio, triglyceride/ HDL ratio, HbA1c, fasting blood sugar, waist circumference, and waist-hip ratio by 39.64, 44.2, 1.284, 2.2, 4.062, 0.682, 3.36, 0.634, and 0.023 units, respectively, for each unit increase in the Mediterranean diet score. The results also show that the HDL- -cholesterol will increase by 7.56 for each unit increase in the Mediterranean diet score. Conclusion: adherence to the Mediterranean diet should be considered a key aspect of public health nutritional strategies to control the increasing prevalence of obesity and metabolic disorders